2020
DOI: 10.1021/acs.orglett.0c01493
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Syntheses of (−)-Fennebricin A, (−)-Renieramycin J, (−)-Renieramycin G, (−)-Renieramycin M, and (−)- Jorunnamycin A via C–H Activation

Abstract: Collective total synthesis of five tetrahydroisoquinoline alkaloids including the first total synthesis of (−)-fennebricin A and (−)-renieramycin J has been accomplished. The synthesis features employing a single common amino acid to symmetrically construct the pentacycle of title alkaloids. The palladium-catalyzed arylation of alanine-derived amide developed by Yu was tactically utilized to afford unnatural amino acid building block rapidly and practically. The structure of synthetic (−)-renieramycin M has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…645 Two research groups reported the semisynthesis of the tetrahydroisoquinoline alkaloid (À)-fennebricin A (Jorunna funebris, nudibranch) starting from jorunnamycin A. 646,647 Both groups reported slight differences in several of the 1 H and 13 C NMR chemical shis and 1 H coupling constants compared to those of the isolated NP, with one group noting these differences and suggesting the need for further conrmation of the actual structure of the NP. 647 Briey highlighted in the Dinoagellate section, but just as relevant to this section, is a call for greater clarity and consistency in reporting paralytic shellsh toxin (PST, e.g.…”
Section: Reviewmentioning
confidence: 99%
“…645 Two research groups reported the semisynthesis of the tetrahydroisoquinoline alkaloid (À)-fennebricin A (Jorunna funebris, nudibranch) starting from jorunnamycin A. 646,647 Both groups reported slight differences in several of the 1 H and 13 C NMR chemical shis and 1 H coupling constants compared to those of the isolated NP, with one group noting these differences and suggesting the need for further conrmation of the actual structure of the NP. 647 Briey highlighted in the Dinoagellate section, but just as relevant to this section, is a call for greater clarity and consistency in reporting paralytic shellsh toxin (PST, e.g.…”
Section: Reviewmentioning
confidence: 99%
“…Li and Lu reported the synthesis of various β-ketosulfones via the ring-opening of cyclobutanone oxime ethers using vinyl triflates, both as a radical acceptor and a source of sulfur dioxide (Scheme 20 ). 28 The generated trifluoromethyl radical abstracts hydrogen from dioxane to give a radical followed by oxidation of the Cu(II) salt. The generated Cu(I) reacts with the oxime to afford an alkyl radical XI , which adds to SO 2 followed by addition to the vinyl triflate.…”
Section: Radical Non-trifluoromethylation Of Vinyl Triflatesmentioning
confidence: 99%
“…As it has been one of the universal synthetic targets of biologically active THIQ marine natural products, to date, one semisynthesis of 50 from safracin B (6B) in six steps (24% overall yield) 60) and five total syntheses of 50 have been achieved. [61][62][63][64][65] All strategies to synthesize a characteristic pentacyclic core are based on electrophilic substitution of the electron-rich arenes, such as the modified Pictet-Spengler cyclization.…”
Section: Transformation Of Renieramycin M Into Jorumycin Via Jorunnamycin Amentioning
confidence: 99%